(untitled) (Research, Society and Development, 2021)
An alternative two-entrance hive system demonstrated here is less taxing for the bee colonies. Bees are directed to forage inside the greenhouse when the crop is in flower, and only have access to the outside after anthesis. Consequently, there are no bees in the greenhouse in the afternoon, facilitating crop management. This system allows the farmer to control bee access to the crop without the need for a smoker or protective equipment. Using this system, we compared pollination by honey bees (Apis mellifera) to hand pollination of zucchini squash (Cucurbita pepo) in greenhouses, during two crop seasons. Data included number of flower visits by the bees, fruit production, and the time and consequent labor costs needed to control bee flight direction versus the costs of hand pollination. In the greenhouses with bees, each female flower received a mean of more than 40 bee visits. When eight or more bees visited a flower, the fruits were significantly heavier than with manual pollination (313 versus 232 g, respectively). Total production was increased 41% with bee pollination. Using bee pollination increased profit over 12%, taking into account hive rental and labor costs for hand pollination versus manipulating the hive entrances.